Short range reconnaissance unmanned aerial vehicle - Kersop, Stefanus Jacobus (North-West University, 2009)
Unmanned aerial vehicles (UAVs) have been used increasingly over the past few years. Special Forces of various countries utilise these systems successfully in war zones such as Afghanistan. The biggest advantage is rapid information gathering without endangering human lives. The South African National Defence Force (SANDF) also identified the need for local short range aerial reconnaissance and information gathering. A detailed literature survey identified various international players involved in the development of small hand-launch UAV systems. Unfortunately, these overseas systems are too expensive for the SANDF. A new system had to be developed locally to comply with the unique requirements, and budget, of the SANDF. The survey of existing systems provided valuable input to the detailed user requirement statement (URS) for the new South African development. The next step was to build a prototype using off-the-shelf components. Although this aircraft flew and produced good video images, it turned out to be unreliable. The prototype UAV was then replaced with a standard type model aircraft, purchased from Micropilot. Some modifications were needed to ensure better compliance with the URS. Laboratory and field tests proved that the aircraft can be applied for aerial images, within range of 10 km from the ground control station (GCS). The major limitation is that it can only fly for 40 minutes. Furthermore, the airframe is not robust, needing repairs after only 15 flights. Although the system has shortcomings, it has already been used successfully. It is expected that improved battery technologies and sturdier light-weight materials will further help to improve the system beyond user specifications.
Thesis (MIng (Electrical Engineering))--North-West University, Potchefstroom Campus, 2010.
Keywords: Unmanned aerial vehicles (UAV); Unmanned aerial systems (UAS); man portable; autopilot; data link; mini-UAV; small UAV; cameras; RF transmitters